KARAKTERISTIK KONSUMEN DAN PERILAKU KONSUMSI DALAM PEMBELIAN PRODUK HASIL PETERNAKAN SAAT PANDEMI COVID-19 - TEVINA EDWIN; A. A. ALIANTA; J. HELLYWARD (Fakultas Peternakan Universitas Udayana, 2021)
The research aimed to measure consumer characteristic and consumption behaviour on purchasing animal product during Covid-19 Pandemic in Padang City, and also to measure the correlation between consumer cha- racteristic and consumption behaviour. The method was a survey with convenience sampling to determine the respondents. Based on that, it determined 150 housewives as respondent. The instrument of this research was qu- estionnaire The data analysed with descriptive quantitative method while the correlation between it analysed with Rank Spearman Test by IBM SPSS 26 Version. The result showed that 84.67% of respondents were small family (family members ?4); 54% of respondents have salary Rp. 2,500,001 until 5,000,000,-/month; 45% respondents was early adult; and 50.67% respondents are undergraduates. The consumption behaviour of animal product du- ring Covid-19 pandemic increased even though it was non-significant. Rank Spearman Test result showed a signifi- cant result (P<0.05). The incomes and education variables were positively correlating with consumption behaviour with Correlation Coefficient 0.205 and 0.234. While family members and negatively correlating with consumption behaviour with Correlation Coefficient -0.176 and -0.184.